Estimating lung cancer mortality attributable to second hand smoke exposure in Germany - Becher, Heiko; Belau, Matthias; Winkler, Volker; Aigner, Annette (International journal of public health, 2018)
ObjectivesPublic health measures such as nonsmoker protection laws affect smoking prevalence and consequently the number of lung cancer deaths attributable to second hand smoke (SHS). In Germany, a risk assessment of SHS has been performed in 1994 only, and therefore, a reassessment is of interest.MethodsBased on current knowledge on the relative risk of lung cancer from SHS, SHS prevalence, lung cancer deaths in Germany, and two approaches to estimate the number of never smokers among lung cancer deaths, we estimated the current number of deaths attributable to SHS among never smokers in Germany.ResultsBased on a relative risk of 1.21 (95% CI 1.14-1.28), recent prevalence of SHS of 39.5% for men and 23.5% for women, the attributable risks are 7.66 and 4.70%, respectively. Out of about 47,000 lung cancer deaths per year, the estimated number of never smokers is about 6000, out of which we estimated 167 being attributable to SHS.ConclusionsDespite an aging population, the number of deaths from lung cancer attributable to SHS decreased considerably. This positive trend should be strengthened by further public health measures.
First Online: 29 July 2017
Gesehen am 13.09.2018